Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Type SC/APC simplex 9° terminated on EN 60793-2-50 of type B-652.D and B-657.A singlemode fibre with full zirconia ferrule, category OP Part 4-3, (19th August 2022) - British Standards Institution,
No abstract available